Techniques of Ozone Monitoring in a Mountain Forest Region: Passive and Continuous Sampling, Vertical and Canopy Profiles - Giacomo Gerosa; Cristina Mazzali; Antonio Ballarin-Denti (The Scientific World Journal)
Ozone is the most harmful air pollutant for plant ecosystems in the Mediterranean and Alpine areas due to its biological and economic damage to crops and forests. In order to evaluate the relation between ozone exposure and vegetation injury under on-field conditions, suitable ozone monitoring techniques were investi-gated. In the framework of a 5-year research project aimed at ozone risk assessment on forests, both continuous analysers and passive samplers were employed during the summer seasons (19941998) in different sites of a wide mountain region (80 x 40 km2) on the southern slope of the European Alps. Continuous analysers allowed the recording of ozone hourly concentration means necessary both to calculate specific exposure indexes (such as AOT, SUM, W126) and to record daily time-courses. Passive samplers, even though supplied only weekly mean concentration values, made it possible to estimate the altitude concentration gradient useful to correct the altitude dependence of ozone concentrations to be inserted into exposure indexes. In-canopy ozone profiles were also determined by placing passive samplers at different heights inside the forest canopy. Vertical ozone soundings by means of tethered balloons (kytoons) allowed the measurement of the vertical concentration gradient above the forest canopy. They also revealed ozone reservoirs aloft and were useful to explain the ozone advection dynamic in mountain slopes where ground measurement proved to be inadequate. An intercomparison between passive (PASSAM, CH) and continuous measurements highlighted the necessity to accurately standardize all the exposure operations, particularly the pre- and postexposure conservation at cold temperature to avoid dye (DPE) activity. Advantages and disadvantages from each mentioned technique are discussed.